Under Pressure: Cetaceans and Fisheries Co-occurrence off the Coasts of Ghana and Côte d'Ivoire (Gulf of Guinea) - de Boer, Marijke N.; Saulino, James T.; Van Waerebeek, Koen; Aarts, Geert (Frontiers in Marine Science, 2016)
Within the Gulf of Guinea high levels of fisheries-related cetacean mortality (bycatch and direct-capture) has been documented. For locally rare species such removals could potentially lead to significant population level effects. However, information on the cetacean abundance and distribution is scarce. Similarly, it remains largely unreported where fishing fleets operate offshore. A cetacean survey took place during geophysical surveys (2013-2014) along the coasts of Ghana and Côte d’Ivoire. This provided a unique opportunity to study both offshore cetacean and fishing communities. Due to large group-sizes, melon-headed whales were the most abundant (0.34 animals km-1) followed by Fraser’s dolphins and short-finned pilot whales. Range state records were confirmed for melon-headed whale and Fraser’s dolphin in Ivoirian waters and ten further species represented first at-sea sightings. The artisanal fishing canoe was most abundant (92% of all vessels) and recorded up to 99.5 km from the Ghanaian coast. Asian trawlers operated over shelf areas and tuna purse-seine vessels in deep oceanic and slope waters. Fraser’s dolphins, melon-headed whales, pantropical spotted dolphins, bottlenose dolphins and pilot whales were recorded in areas with the highest fishing densities. Melon-headed whales, pilot whales and rough-toothed dolphins were observed in vicinity of trawlers; bottlenose dolphins, pantropical spotted dolphins and pilot whales in vicinity of canoes. Some notable differences were found in the species composition between the present surveys and port-based surveys of landed cetaceans (bycatch/direct-captures). These may be explained by (1) feeding strategies (nocturnal vs. diurnal; surface vs. deep water); (2) different attractions to vessels/fishing gear; (3) variable body sizes; and (4) difficulty to positively identify species. Despite these differences, both cetaceans and fishing vessels predominantly occurred in shelf and slope waters (< 1,000 m depth contour), making fishery-related mortality likely. The poor knowledge on population trends of cetaceans in this unique upwelling region, together with a high demand for cetacean products for human consumption (as ‘marine bushmeat’) may lead to a potential decline of some species that may go unnoticed. These new insights can provide a foundation for the urgently required risk assessments of cetacean mortality in fisheries within the northern Gulf of Guinea.